A Note on the Effects on Unemployment Insurance, Minimum Wage Legislation and Trade Union Growth on Reported Unemployment Rates in Canada, 1950-1975 - Grubel, Herbert; Maki, Dennis (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1981)
The paper analyzes the effects of the factors noted in the title on reported unemployment rates, both theoretically and empirically. The implications of the results for the natural rate debate and macroeconomic stabilization policies are briefly discussed.